IOT based novel session payment system - Roja, G.; Pushpa Rani, K.; Sabitha, Ch.; Dhanalaxmi, B.; Sreeja, S. (International Journal of Engineering and Technology, 2018)
A remote technique has been intended to process a money related installment effectively. The users can simply use their charge/visas at the counter and all the preparing required should be completed consistently. An advanced mobile phone is a notable device to tolerate. There is an issue of carrying such a significant number of charge/visas in a wallet. Cell phone is the best gadget to convey charge/visas electronically. The present paper gives on an electronic charge/visas in a smart phone and move to IoT cash. A novel session installment framework utilizing IoT cash should be acquainted with limit charge/visas chance. The degree of present paper is confined into the protection appear for a straightforward installment structure utilizing Internet of Things (IoT). Because every IoT cash is uncommon for every installment, here period installment procedure will encourage weight at anchoring the directory of installment structure.